2016
DOI: 10.1155/2016/7293626
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine for the Treatment of Vascular Dementia: An Overview of Scientific Evidence

Abstract: Dementia is a leading cause of mental and physical disability. Vascular dementia (VaD) is the second most common cause of dementia after Alzheimer's disease (AD) constituting 10–15% of the dementia population. Currently there are no approved pharmaceutical options for VaD and the conventional anti-AD therapies provide only modest, short-term relief of symptoms associated with VaD. Herbal medicines have been used for the management of dementia-like symptoms for centuries and may provide viable therapies for VaD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(117 citation statements)
references
References 87 publications
(97 reference statements)
1
116
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), including Chinese herbal medicines (CHM) and acupuncture, with its unique theory and long history, has been used for the management of cardiovascular diseases for thousands of years in China. In recent years, there has been an increasing recognition of the health benefits of CHM, which are supported mounting evidence from pre-clinical and clinical studies ( 15 17 ). Traditionally, CHM is prescribed in the form of mixtures of plant, animals or minerals and often contains numerous bioactive components.…”
Section: Introductionmentioning
confidence: 90%
“…Traditional Chinese medicine (TCM), including Chinese herbal medicines (CHM) and acupuncture, with its unique theory and long history, has been used for the management of cardiovascular diseases for thousands of years in China. In recent years, there has been an increasing recognition of the health benefits of CHM, which are supported mounting evidence from pre-clinical and clinical studies ( 15 17 ). Traditionally, CHM is prescribed in the form of mixtures of plant, animals or minerals and often contains numerous bioactive components.…”
Section: Introductionmentioning
confidence: 90%
“…Also, to the best of our knowledge, studies recent to on ancient Chinese herbal medicine and molecular biology in the treatment of myocardial infarction have been undertaken [4,5]. As well as additional studies confirmed the use of herbal medicine for the treatment of vascular dementia [6].…”
Section: Introductionmentioning
confidence: 96%
“…The SLT formula consists of specific dosages of standardised ginkgo, ginseng, and saffron extracts, designed for the management of cognitive impairments. The data from a series of preclinical and clinical studies show that SLT can affect multiple therapeutic targets associated with MCI and dementia [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLT represents a new generation of herbal formulations for which the chemical and pharmacological profiles have been clearly defined using analytical chemistry, pharmacognosy, and pharmacology techniques. The preclinical research contributing to the development and standardisation of SLT [ 23 – 30 ], the mechanisms of action of the three herbs [ 23 , 31 – 38 ], and findings from clinical studies [ 22 , 39 48 ] have all been described thoroughly elsewhere and summarised in a recent review by Chang et al [ 23 ]. Table 1 details the multiple pharmacological targets that the active components in SLT address relevant to the pathophysiology of MCI.…”
Section: Introductionmentioning
confidence: 99%